\(\frac{1}{10\times11}+\frac{1}{11\times12}+...+\frac{1}{99\times100}\)

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 1 2017

\(A=\frac{1}{10\times11}+\frac{1}{11\times12}+...+\frac{1}{99\times100}\)

\(A=\frac{1}{10}-\frac{1}{11}+\frac{1}{11}-\frac{1}{12}+...+\frac{1}{99}-\frac{1}{100}\)

\(A=\frac{1}{10}-\frac{1}{100}\)

\(A=\frac{9}{100}\)

25 tháng 1 2017

\(A=\frac{1}{10.11}+\frac{1}{11.12}+...+\frac{1}{99.100}\)

\(=\frac{1}{10}-\frac{1}{11}+\frac{1}{11}-\frac{1}{12}+...+\frac{1}{99}-\frac{1}{100}\)

\(=\frac{1}{10}-\frac{1}{100}\)

\(=\frac{9}{100}\)

27 tháng 1 2017

a)\(VT=\frac{1}{2\cdot5}+\frac{1}{5\cdot8}+...+\frac{1}{\left(3n-1\right)\left(3n+2\right)}\)

\(=\frac{1}{3}\left[\frac{3}{2\cdot5}+\frac{3}{5\cdot8}+...+\frac{3}{\left(3n-1\right)\left(3n+2\right)}\right]\)

\(=\frac{1}{2}-\frac{1}{5}+\frac{1}{5}-\frac{1}{8}+...+\frac{1}{3n-1}-\frac{1}{3n+2}\)

\(=\frac{1}{2}-\frac{1}{3n+2}=\frac{3n+2}{2\cdot\left(3n+2\right)}-\frac{2}{2\cdot\left(3n+2\right)}\)

\(=\frac{3n+2-2}{6n+4}=\frac{3n}{6n+4}=VP\)

27 tháng 1 2017

chết phần a quên nhân vs 1/3

12 tháng 11 2016

A=33. \(\left(1-\frac{2}{3}\right)\left(1-\frac{2}{5}\right)...\left(1-\frac{2}{99}\right)\)

A=33.\(\frac{1}{3}.\frac{3}{5}....\frac{97}{99}\)

A=33.\(\frac{1}{99}\)

A=\(\frac{33}{99}=\frac{1}{3}\)

18 tháng 8 2020

a) \(-\frac{8}{18}-\frac{15}{27}=-\frac{4}{9}-\frac{5}{9}=\frac{-9}{9}=-1\)

b) \(\frac{19}{24}-\left(-\frac{1}{2}+\frac{7}{24}\right)\)

\(=\frac{19}{24}+\frac{12}{24}-\frac{7}{24}=\frac{24}{24}=1\)

c) \(P=\frac{3^{11}.11+3^{11}.21}{3^9.2^5}\)

\(P=\frac{3^{11}.\left(11+21\right)}{2^9.2^5}=\frac{3^{11}.32}{2^9.32}=3^2=9\)

d) \(\frac{2}{1.2}+\frac{2}{2.3}+\frac{2}{3.4}+...+\frac{2}{99.100}\)

\(=2\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{99}-\frac{1}{100}\right)\)

\(=2\left(1-\frac{1}{100}\right)\)

\(=2.\frac{99}{100}=\frac{99}{50}\)

Bài 2: 

a: =>x/7=1/21

=>x=1/3

c: =>x(3x-2)=0

=>x=0 hoặc x=2/3

Bài1:

a: \(=\left(-\dfrac{7}{3}\right)^{3-2}=\dfrac{-7}{3}\)

b: \(=\left(-\dfrac{4}{9}\right)^{1-3}=\left(-\dfrac{4}{9}\right)^{-2}=\dfrac{81}{16}\)

c: \(=\left(\dfrac{1}{5}\right)^{10-7}=\left(\dfrac{1}{5}\right)^3=\dfrac{1}{125}\)

11 tháng 7 2019

1) ( \(\frac{55}{3}\): 15 + \(\frac{26}{3}\) . \(\frac{7}{2}\)) : [(\(\frac{37}{3}\) + \(\frac{62}{7}\)) . \(\frac{7}{18}\)] : \(\frac{-1704}{445}\)

= ( \(\frac{55}{3}\). \(\frac{1}{15}\) + \(\frac{91}{3}\)) : [ \(\frac{445}{21}\) . \(\frac{7}{18}\)] . \(\frac{-445}{1704}\)

= ( \(\frac{11}{9}\)+ \(\frac{91}{3}\)) : \(\frac{445}{54}\). \(\frac{-445}{1704}\) = \(\frac{284}{9}\). \(\frac{54}{445}\). \(\frac{-445}{1704}\)

= \(\frac{284}{9}\). (\(\frac{54}{445}\). \(\frac{-445}{1704}\))

= \(\frac{284}{8}\). \(\frac{-9}{284}\)

= \(\frac{-9}{8}\)